Strengthening of the Laboratories of the University of Guayaquil - Rios, Rafael (Revista Universidad de Guayaquil, 2009)
Accreditation of tests from the Quality Control of Water, Petroleum, and Environment Laboratory of the Faculty of Chemical Engineering.Accreditation of tests from the Food Laboratory of the Technological Research Institute of the Faculty of Chemical Engineering. The process of standard 17025 was financed by Corpei through the management of CTT-UG.Implementation of standard 17025 in the Laboratory of the Natural Resources Research Institute of the Faculty of Natural Sciences, currently undergoing audit and soon to be accredited. This process was co-financed by Swisscontact through the management of CTT-UG.» Organization for Accreditation and implementation of standard 17025 in the PROGECA Laboratory - Quality Management Program of the Faculty of Chemical Sciences.